Herpes Simplex Virus Type 1 Infection of the Central Nervous System: Insights Into Proposed Interrelationships With Neurodegenerative Disorders - Duarte, Luisa F.; Farías, Mónica A.; Álvarez, Diana M.; Bueno, Susan M.; Riedel, Claudia A.; González, Pablo A. (Frontiers in Cellular Neuroscience, 2019)
Infection with herpes simplex virus type 1 (HSV-1) is highly prevalent in the human population with most of the infected asymptomatic. Importantly, HSV-1 can infect the brain by reaching neurons in the trigeminal ganglia and without evident clinical symptoms. Once in the brain, the virus can either reside in a quiescent latent state in this tissue, or eventually actively lead to severe acute necrotizing encephalitis, which is characterized by exacerbated neuroinflammation and prolonged neuroimmune activation producing life-threatening disease. Although HSV-1 encephalitis can be treated with antivirals that limit virus replication, neurological sequelae are common and the virus will nevertheless remain in the this tissue. Importantly, there is accumulating evidence that suggests that HSV-1 infection of the brain, in both symptomatic and asymptomatic individuals can lead to multiple neurodegenerative disorders. Here, we review and discuss acute and chronic infection of specific brain regions with HSV-1 and how this infection may affect neuron and cognitive functions in the host. We review potential cellular and molecular mechanisms leading to neurodegeneration, such as protein aggregation, dysregulation of autophagy, oxidative cell damage and apoptosis, among others. Furthermore, we discuss the impact of HSV-1 infection over brain inflammation and its potential relationship with neurodegenerative diseases.